2015
DOI: 10.1093/neuonc/nov083
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalation study of the PI3K/mTOR inhibitor voxtalisib (SAR245409, XL765) plus temozolomide with or without radiotherapy in patients with high-grade glioma

Abstract: Voxtalisib in combination with TMZ with or without RT in patients with high-grade gliomas demonstrated a favorable safety profile and a moderate level of PI3K/mTOR pathway inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Cloughesy et al (28) administered voxtalisib (XL765), a pan PI3K/mTOR inhibitor or XL147, a pan PI3K inhibitor, to patients with recurrent glioblastoma and showed that voxtalisib had better tumor penetration than XL147, although both drugs produced significant reduction of pS6K1 compared to archived tumor and reduction of Ki-67, suggesting that some inhibition of the PI3K pathway was achieved. Wen et al (29) subsequently conducted a Phase I trial of voxtalisib with temozolomide, with or without radiation therapy in patients with high-grade gliomas. The MTD was 90 mg once daily or 40 mg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…Cloughesy et al (28) administered voxtalisib (XL765), a pan PI3K/mTOR inhibitor or XL147, a pan PI3K inhibitor, to patients with recurrent glioblastoma and showed that voxtalisib had better tumor penetration than XL147, although both drugs produced significant reduction of pS6K1 compared to archived tumor and reduction of Ki-67, suggesting that some inhibition of the PI3K pathway was achieved. Wen et al (29) subsequently conducted a Phase I trial of voxtalisib with temozolomide, with or without radiation therapy in patients with high-grade gliomas. The MTD was 90 mg once daily or 40 mg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that used temsirolimus as maintenance therapy in castration-resistant prostate cancer after docetaxel induction, the regimen proved safe, and delayed the time to treatment failure to 6 months [274]. Voxtalisib plus temozolomide, an alkylating agent, with or without radiotherapy also displayed a favorable safety profile and moderate amount of PI3K/mTOR pathway inhibition in patients with high-grade glioma [275]. Based on these clinical trial results, combining mTOR inhibition with conventional cytotoxic chemotherapy warrants further investigation.…”
Section: Combining Mtor Inhibition With Conventional Chemotherapies Amentioning
confidence: 99%
“…The dosage used typically varies between 40 and 60 Gy divided into daily fractions of 1.8–10 Gy depending on tumor size, metastases, invasiveness and possible side effects [ 12 , 13 ]. In many clinical protocols, the radiation therapy accompanies treatment with the protein kinase inhibitor drugs, in different combinations [ 14 17 ]. Since the clinical trials of TKIs and rapalogs for the ovarian cancer and the neuroblastoma are still in progress, we aimed to investigate if this treatment may cooperate or interfere with the radiation therapy, thus altering its efficiency.…”
Section: Introductionmentioning
confidence: 99%